Independent Curriculum Learning Plan of Reading and Writing in Inclusive Schools - Liyya Mutimmatud Daroini; Luluk Sri Agus Prasetyoningsih (Jurnal Pendidikan Anak, 2022)
This study aims to explore the planning of ATP and teaching modules for grade 1 literacy learning with independent learning curriculum at the inclusive school of SDN Sumbersari 2 Malang. This study uses a qualitative approach. Sources of data used by researchers in the form of ATP documentation and Indonesian Language Teaching Module in class I SDN Sumbersari 2 Malang. Data collection is done by means of documentation and interview techniques. The results showed that there was no difference in planning for literacy learning in the form of ATP (Learning Objectives Flow) and Teaching Modules designed by teachers for regular students, hyperactivity/ADHD and mild hearing loss. Teachers use ATP (Learning Objectives Flow) from the Ministry of Education and Culture, teachers do not modify ATP (Learning Objectives Flow) for hyperactive students and mild hearing loss. Teachers design Teaching Modules that are in accordance with teacher handbooks published by the Ministry of Education and Culture. Teachers also do not design/modify special teaching modules for hyperactive/ADHD and mild hearing-impaired students.